2006
DOI: 10.1016/j.jprocont.2005.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Alternative solutions to multi-variate control performance assessment problems

Abstract: Performance assessment of multi-variate control with minimum variance control as the benchmark requires an interactor matrix to filter the closed-loop output. This is to transfer the coordinate of the original variables into a new one in order to identify the control invariant disturbance dynamics from the first few terms of the closed-loop output Markov parameters. There has been a great deal of interest to simplify this approach, in particular, to find methods that do not need the interactor matrix. With thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
(54 reference statements)
0
34
0
Order By: Relevance
“…Next, we give the switched system measurement data tensor space representation, which is a fundamental step for switched control system performance benchmark estimation. Then, we can extend the data-driven subspace approach for multivariate linear systems in [35] to tensor space modeling Figure 5. Unfolding for tensor space modeling F of switched system operator with additive disturbance including three subsystems, and each subsystem has three inputs and three outputs.…”
Section: Performance Benchmark Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we give the switched system measurement data tensor space representation, which is a fundamental step for switched control system performance benchmark estimation. Then, we can extend the data-driven subspace approach for multivariate linear systems in [35] to tensor space modeling Figure 5. Unfolding for tensor space modeling F of switched system operator with additive disturbance including three subsystems, and each subsystem has three inputs and three outputs.…”
Section: Performance Benchmark Estimationmentioning
confidence: 99%
“…The representation shows that this tensor space modeling is quite general, it can capture logical switching feature, for example, the interaction nature of control and protection systems for safety-important process. Consequently, the data-driven performance benchmark estimation algorithm based on higher-order singular value decomposition that extends subspace approach [8,35] can be derived for the calculation of control performance benchmark for performance measure. Moreover, by using orthogonal projection in tensor space, the prediction error method formulation of a performance benchmark estimation procedure is then presented for the switched control system performance assessment, which is solvable using Tensor Toolbox for MATLAB.…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrates the multiobjective and often conflicting objective of maximizing both the set-point tracking and disturbance rejection ability of the control strategy and tuning parameters. Studies have shown that while the ITAE criterion is useful as an objective function for set-point tracking, an objective function that incorporates both the ITAE and minimum variance control (MVC) should be employed to take into account disturbance rejection as well [53]. MVC is a useful benchmark to maximize the disturbance rejection ability.…”
Section: Case 4: Effect Of Stochastic Disturbancesmentioning
confidence: 99%
“…Among these methods, prediction error approach is one of the most promising ones which does not need the interactor matrix. Because the concepts of prediction error approach and closed-loop potentials as defined in [28] play an important role in determining the performance of nitrate cascade controllers, we describe these concepts in detail in the following part.…”
Section: Control Performance Assessmentmentioning
confidence: 99%